Differences of performance in nasal allergen challenge with latex allergen extract - Chełmińska, Marta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Health care workers are at high risk of developing an allergy to latex. Some of them do not know that latex gloves or other latex products are the reason for their symptoms. We always have to do skin prick tests with latex allergens and sIgE in all cases in which symptoms occurred after contact with latex products. If we have diagnostic problems we have to do provocation tests on the site (skin, conjunctiva, nose or bronchi) where the symptoms occurred. If patients have symptoms after contact with latex products without sensitization (SPT negative and sIgE < 0.35 kU/l) we have to do provocation tests. In some cases we have to do patch tests with rubber and its components.